Maximizing the Role of Coaches in Implementing Social Values in Team Sports - Eko Purnomo; Nina Jermaina; Agus Gumilar; Mutiara Felicita Amsal; Andri Gemaini; Amin Akbar; Rila Muspita; Nor Eeza Zainal Abidin (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
ntroduction: The coach is critical to the success of the training program and serves as the driving force to steer the team in the direction they want. Therefore, coaches are very vital and must understand players, program creation and also program implementation in the field. The program designed by the coach should not only prioritize and improve sports skills. Coaches must also instill values that can uphold the sportsmanship of each individual or team.